Combined Replacement of Fishmeal and Fish Oil by Poultry Byproduct Meal and Mixed Oil: Effects on the Growth Performance, Body Composition, and Muscle Quality of Tiger Puffer - Lili Zhao; Lin Li; Feiran Zhang; Peng Li; Yanlu Li; Jian Liu; Yuliang Wei; Mengqing Liang; Qiang Ma; Houguo Xu (Aquaculture Nutrition)
This study aimed to evaluate the effects of combined replacement of fishmeal (FM) and fish oil (FO) with poultry byproduct meal (PBM) and mixed oil (MO, poultry oil: coconut oil = 1 : 1) on growth performance, body composition and muscle quality of tiger puffer (Takifugu rubripes). Fish with an average initial body weight of 14.29 g were selected for the feeding experiment. FM accounting for 0%, 5%, and 10% of the diet was replaced by PBM. For each grade of FM replacement, 5% FO or MO was used as added oil. The six experimental diets were designated as FO-FM, MO-FM, FO-5PBM, MO-5PBM, FO-10PBM, and MO-10PBM, respectively. Each treatment was performed in triplicate with 30 fish per replicate. The feeding period was 45 days. There was no significant difference in growth performance among the groups. Dietary supplementation of both PBM and MO had marginal effects on whole-fish proximate composition, except that dietary MO supplementation significantly increased the liver moisture content. In serum, there were no significant differences in contents of triglyceride, total cholesterol, total bile acid, and protein carbonyl among groups, but the malondialdehyde content was reduced by MO. The fatty acid composition in fish mirrored those in the diets, but the omega-3 sparing effects of saturated and monounsaturated fatty acid in MO can still be observed. Dietary PBM and MO had marginal effects on free amino acid composition and texture of fish muscle, but exerted complicated effects on the muscle volatile flavor compound composition. In conclusion, combined fishmeal (10% of the diet) and fish oil (5% of the diet) replacement with poultry byproduct and mixed oil (poultry oil + coconut oil) had no adverse effects on the growth performance and body proximate composition of farmed tiger puffer. However, these replacements changed the muscle flavor compound profile.